2009
DOI: 10.1007/s11814-009-0223-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of additive chemicals on the viscosity of coal-petroleum coke-water slurry fuel for a gasification process

Abstract: As a preliminary study for the gasification of an anthracite and petroleum coke mixture, viscosity was measured at various temperatures (20-50 o C), slurry concentrations (60-70 wt%) and additive amounts (0-0.8 wt%) by using an LV-II type viscometer. In addition, four types of different additives, sodium naphthalene sulfonate, poly(methyl methacrylate), polypropylene and a polypropylene glycol based additive, were applied to Korean anthracite, petroleum coke and mixtures of these materials, and the viscosity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
3
2
0
Order By: Relevance
“…Increasing the F127 concentration beyond this point seemed to have little to no effect on the slurry’s viscosity after its negligible yield stress. Other dispersants (PVA, PEO, and PCA) were measured to have approximately the same minimum concentration to take effect, and minimum dispersant concentrations have been observed previously in other slurry systems. ,, The minimum dispersant concentration is thought to be an effect of adsorbing enough polymer onto the surface of the petcoke to make a complete and sufficiently dense and uniform monolayer.…”
Section: Results and Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Increasing the F127 concentration beyond this point seemed to have little to no effect on the slurry’s viscosity after its negligible yield stress. Other dispersants (PVA, PEO, and PCA) were measured to have approximately the same minimum concentration to take effect, and minimum dispersant concentrations have been observed previously in other slurry systems. ,, The minimum dispersant concentration is thought to be an effect of adsorbing enough polymer onto the surface of the petcoke to make a complete and sufficiently dense and uniform monolayer.…”
Section: Results and Discussionsupporting
confidence: 68%
“…This density is close to the 60 vol % theoretical maximum volume fraction for randomly packed monodisperse spheres. Work by Yoon et al with petcoke–coal mixture slurries reported that the ionic and anionic dispersants tested were roughly equally effective for petcoke . This work supports this claim except for the enhanced performance by F127.…”
Section: Results and Discussionsupporting
confidence: 67%
See 3 more Smart Citations